2009
DOI: 10.1177/147323000903700329
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End-products Enhance Calcification in Vascular Smooth Muscle Cells

Abstract: Advanced glycation end-products (AGEs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 15 publications
3
47
0
Order By: Relevance
“…4). Expression of RAGE was examined by immunohistochemistry, because the AGE-RAGE axis has been shown to play an important role in vascular calcification in type 2 diabetes [10,11,12,13]. As shown in figure 3, RAGE expression was increased in the aorta of hyperglycemic, uremic/hyperglycemic and uremic rats, but not in the aorta of control rats.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Expression of RAGE was examined by immunohistochemistry, because the AGE-RAGE axis has been shown to play an important role in vascular calcification in type 2 diabetes [10,11,12,13]. As shown in figure 3, RAGE expression was increased in the aorta of hyperglycemic, uremic/hyperglycemic and uremic rats, but not in the aorta of control rats.…”
Section: Resultsmentioning
confidence: 99%
“…In cultured vascular SMCs, AGEs induced expression of osteopontin, Runx2 and alkaline phosphatase as well as calcium deposition [10,11]. These AGE-mediated changes were partially attenuated by a neutralizing antibody to the receptor for AGE (RAGE).…”
Section: Introductionmentioning
confidence: 99%
“…RAGE not only promotes atherosclerosis and diabetic cardiovascular and renal complications [17,18,19,20,21,22], but also mediates chondrocyte differentiation [23,24]. Furthermore, recent studies have revealed the capacity of AGEs to induce calcification by cultured SMCs and pericytes mediated by RAGE signaling [25,26,27]. RAGE signaling can be suppressed via ligand sequestration by endogenous secretory and endoproteolytically released soluble RAGE (sRAGE) [18,19,28,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…These AGE-mediated changes in vascular smooth muscle cells were partially attenuated by a neutralizing antibody to RAGE. 19 AGE has also been shown to accelerate vascular calcification through the RAGE/ oxidative stress pathway in an animal model of diabetic vascular calcification. 20 Thus, our current novel clinical observations add to the growing experimental evidence linking AGE to vascular calcification and support the involvement of tissue AGE in the process of vascular calcification in CKD and diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%